Microstructural and Fractographic Characterization of a Thermally Embrittled Nuclear Grade Steel: Part I - Annealing - Tarpani José R.; Braz Maria H.P.; Bose Filho Waldek W.; Spinelli Dirceu (Materials Research, 2002)
A nuclear reactor pressure vessel steel was submitted to different annealing heat treatments aimed at simulating neutron irradiation damage. The obtained microstructures were mechanically tested with subsequent metallographic and fractographic characterization. The relevant microstructural and fractographic aspects were employed in the interpretation of the mechanical behavior of the microstructures in both quasi-static (J-R curve) and dynamic (Charpy impact) loading regimes. A well defined relationship was determined between the elastic-plastic fracture toughness parameter J-integral and the Charpy impact energy for very most of the microstructures.